2020
DOI: 10.1111/btp.12834
|View full text |Cite
|
Sign up to set email alerts
|

Human disturbance and the activity patterns and temporal overlap of tapirs and jaguars in reserves of NW Belize

Abstract: Wild animals may perceive humans as potential threats and consequently change their behavior to avoid us (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Our results support these findings in that seasonal antipredator behaviour aligned with competing risk for deer. While humans may induce antipredator behaviour in prey (Gehr et al, 2017; Monette et al, 2020; Xiao et al, 2018), panthers represent a significant source of mortality for deer, accounting for 72% of deer mortalities compared to a minimal 0.01% attributed to humans (Bled et al, 2022). Therefore, as flooding recedes, deer may perceive humans as a lesser source of mortality compared to panthers and adjust their temporal activity to minimize risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support these findings in that seasonal antipredator behaviour aligned with competing risk for deer. While humans may induce antipredator behaviour in prey (Gehr et al, 2017; Monette et al, 2020; Xiao et al, 2018), panthers represent a significant source of mortality for deer, accounting for 72% of deer mortalities compared to a minimal 0.01% attributed to humans (Bled et al, 2022). Therefore, as flooding recedes, deer may perceive humans as a lesser source of mortality compared to panthers and adjust their temporal activity to minimize risk.…”
Section: Discussionmentioning
confidence: 99%
“…Mammals are known to shift their spatiotemporal activity patterns to avoid anthropogenic stress (Monette et al, 2020). Schuette et al (2013), indicate lower apex predator occupancy in more human dominated areas owing to heavy human land‐use.…”
Section: Discussionmentioning
confidence: 99%
“…Apex carnivores such as tigers Panthera tigris and leopards P. pardus synchronize their activity patterns to overlap with their principal prey, whereas meso‐predators such as Asiatic wild dogs Cuon alpinus adjust their activity to avoid competition with larger carnivores and minimize kleptoparasitism while opportunistically exploiting prey (Karanth & Sunquist, 2000; Palomares & Caro, 1999; Ramesh et al, 2012). In addition, anthropogenic factors are widely acknowledged as a major threat to mammal temporal activity patterns (Bhatt et al, 2021; Monette et al, 2020). Several studies have found that mammal temporal activity patterns are influenced by the activity of humans and domesticated animals, particularly livestock and dogs (Díaz‐Ruiz et al, 2016; Gaynor et al, 2018; Mella‐Méndez et al, 2019; Podgórski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that tapirs show little plasticity to alter their behavior, with similar activity patterns [ 130 ] or movement patterns [ 31 ] in areas under different human disturbances. Whether the species needs to tolerate human activities or can adapt avoidance strategies seems to depend on the intensity of human use.…”
Section: Discussionmentioning
confidence: 99%